PENGARUH MODEL PEMBELAJARAN ICM BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD - Fera Yunita; Deki Wibowo; Manggalastawa Manggalastawa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study was conducted to analyze the impact of applying the Index Card Match learning model combined with Audio-Visual video media to improve the learning outcomes of fifth-grade students at SD 1 Panjang. The background of this research originated from the low academic achievement of students, which was suspected to be caused by the lack of student activeness during the learning process and the use of monotonous teaching methods. This study employed a quantitative approach with an experimental method, using a pre-experimental one-group pretest–posttest design. The research subjects consisted of 30 fifth-grade students selected using a saturated sampling technique. Data were collected through interviews, tests (pretest and posttest), questionnaires, and documentation. The analysis results showed an increase in the average learning outcome score from 43.17 before the treatment to 87.67 after the implementation of the learning model. Based on the linear regression test with a significance level of 0.00, which is less than 0.05, it indicates that variable X influences variable Y. The paired sample t-test also showed a significance value of 0.00, meaning that there is an effect of variable X on variable Y. Thus, it can be concluded that the Index Card Match model assisted by Audio-Visual media affects the learning outcomes of fifth-grade elementary school students. The improvement in learning outcomes through the Index Card Match model can also be seen from the N-Gain test, which shows that 9 students fall into the medium category and 21 students fall into the high category, indicating that the normalized N-Gain was achieved. The classical completeness test showed 100% mastery, meaning that more than 75% of students achieved scores above the Minimum Mastery Criteria (KKM). It is concluded that the Index Card Match learning model assisted by Audio-Visual media, with the material “Norms in My Life,” resulted in students achieving scores that met or exceeded the KKM. If you'd like, I can refine this version to make it more academic or suitable for journal publication. ABSTRAK Penelitian ini dilaksanakan untuk menganalisis dampak penerapan model pembelajaran Index Card Match yang dipadukan dengan media video Audio Visual untuk meningkatan hasil belajar siswa kelas V di SD 1 Panjang. Latar belakang penelitian ini berawal dari rendahnya capaian akademik siswa, yang diduga disebabkan oleh kurangnya keaktifan siswa selama proses pembelajaran serta penggunaan metode mengajar yang cenderung monoton. Penelitian ini menggunakan pendekatan kuantitatif dengan metode eksperimen, yakni desain pre-eksperimental one group pretest-posttest. Subjek penelitian terdiri dari 30 siswa kelas V yang diambil menggunakan teknik sampel jenuh. Data dikumpulkan melalui wawancara, tes (pretestdan posttest), angket, serta dokumentasi. Hasil analisis menunjukkan adanya peningkatan skor rata-rata hasil belajar dari 43,17 sebelum perlakuan menjadi 87,67 setelah penerapan model pembelajaran. Berdasarkan uji regresi linier dengan taraf 0,00 atau kurang dari 0,05 yang artinya variabel x berpengaruh terhadap variabel y. Uji paired sample t-test dengan taraf signifikan 0,00 atau kurang dari 0,05 yang artinya adanya pengaruh variabel x terhadap variabel y. Jadi dapat disimpulkan adanya pengaruh model Index Card Match berbantuan media Audio Visual terhadap hasil belajar siswa kelas V sekolah dasar. Peningkatan hasil belajar melalui model Index Card Match dapat dilihat melaui uji N-Gain bahwa siswa dengan kategori sedang ada 9 anak, dan siswa dengan kategori tinggi ada 21 siswa. Yang artinya N-Gain ternomalisasi. Uji ketuntasan klasikal di nyatakan 100% tuntas atau di atas KKM, yaitu lebih dari 75% siswa yang tuntas. Disimpulkan bahwa model pembelajaran Index Card Match berbantuan media Audio Visual dengan materi norma dalam kehidupanku nilai siswa dinyatakan tuntas atau di atas KKM.